49. KNOWLEDGE, ATTITUDES, AND PRACTICES REGARDING HAND, FOOT, AND MOUTH DISEASE PREVENTION AND ASSOCIATED FACTORS AMONG MOTHERS OF CHILDREN UNDER FIVE YEARS OLD IN XUYEN MOC DISTRICT, BA RIA - VUNG TAU PROVINCE (Vietnam Journal of Community Medicine, 2025)
Objective: To determine the proportion of appropriate knowledge, attitudes, and practices regarding the prevention of hand foot and mouth disease and identify associated factors among mothers of children under five years old in Xuyen Moc district, Ba Ria - Vung Tau province.Method: A cross-sectional analytical study was conducted among 300 mothers with children under five years old from November 2024 to March 2025.Results: The study showed that 46.33% of mothers had appropriate knowledge about hand foot and mouth disease prevention, 96.67% had a positive attitude, and 74.33% demonstrated appropriate preventive practices. Educational level was significantly associated with knowledge (OR = 2.30; p = 0.001) and practices (OR = 3.40; p = 0.001). Moreover, mothers under 35 years old were more likely to engage in appropriate preventive practices (OR = 2.28; p < 0.002).Conclusion: There were significant differences in the levels of knowledge, attitudes, and practices regarding hand foot and mouth disease prevention. Although attitudes and practices were relatively high, the proportion of mothers with accurate knowledge remained low and requires improvement. Special attention should be paid to enhancing hand foot and mouth disease - related knowledge and practices among mothers with lower educational levels and older age.
Keywords: Hand foot and mouth disease; knowledge; attitudes; practices; children under five years old.